Influência do tipo de prótese total dupla na função mastigatória - Franciozi, Marcos Antônio (2013)
The objective of this experiment was to evaluate the masticatory efficiency and pattern of activation of the muscles of mastication, in three separate stages, the first tests were done with the prosthesis in use, the second prosthesis with posterior crossbite, prostheses and third occlusion bilateral balanced experimental clinical trial, non-randomized, cross. We selected 20 patients, 4 males and 16 females aged between 44 and 87 years, mean 67.1, all denture wearers double to more than 5 years and not more than 10 years. The results were recorded and on which statistical tests were applied using the program PAST version 2.15 ("paired t test"), and analysis of variance (ANOVA). In the evaluation of the data using analysis of variance (ANOVA) showed similarity between the results obtained, however the assessment with the paired t test, applied to electromyographic results, the right temporal muscle showed statistical significance in the comparison between prosthesis use versus prosthesis with posterior crossbite and prosthesis use versus bilateral balanced occlusion and left masseter muscle when comparing posterior crossbite versus bilateral balanced occlusion. The fragmentation of food artificial test showed statistical significance between the prostheses in use versus the dentures with balanced occlusion bilateral. We can conclude that the best results were obtained with the new prostheses, both tests fragmentation of artificial food, such as activation of masticatory muscles